A casemix study of patients seen by a dermatology trainee in rural and urban outpatient settings. (30th December 2014) - Tilakaratne, Dev; Warren, Lachlan; Menz, Jennifer
Abstract: Background/Objectives: For 8 years South Australian dermatologists have provided an outreach service to the Northern Territory (NT), including rural and remote areas. In 2012 and 2013, a trainee accompanied a dermatologist on these outreach visits. This is the first prospective study that documents the spectrum of dermatological diseases requiring outpatient specialist input in various settings in the NT, and also the first study to compare the clinical experience of one Australian dermatology trainee in urban and rural settings. Materials and Methods: Characteristics of patients managed primarily by the outreach dermatology registrar were recorded prospectively from February 2013 to July 2013. The data from the trainee's urban encounters were compared to that of the rural centres. The spectrum of conditions seen in these two settings was placed in the disease categories specified in the Australasian College of Dermatologists (ACD) curriculum. Results: The Royal Adelaide Hospital outpatient experience provided greater exposure to skin neoplasms, lymphoproliferative and myeloproliferative disorders and non‐infectious neutrophilic/eosinophilic disorders. The outreach sites provided greater exposure to infections, adnexal diseases and genodermatoses. Both urban and rural experiences provided a broad exposure to the disease categories outlined in the ACD curriculum. Conclusions: The spectrum of disease requiring specialist dermatology input varies between urban South Australia and rural NT. The inclusion of dermatology trainees in outreach visits broadens their clinical exposure. It is recommended that other dermatology service providers in Australia consider documenting clinical casemix comparisons to assess dermatology demand, outcomes and trainee exposure.